2017
DOI: 10.5334/gjgl.111
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental prepositions and case: Contexts of occurrence and alternations with datives

Abstract: We will argue that instrumentals are the mirror image of dative/genitive obliques. We propose that both sets of adpositions/cases are elementary predicates, expressing a zonal inclusion (partwhole/possession relation); instrumentals reverse the direction of the relation with respect to datives/genitives. Our claim is that with-type morphemes provide very elementary means of attaching extra participants (themes, initiators, etc.) to events (VP or vP predicates) -with specialized interpretations derived by pragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…2 It is important to notice, for the purposes of our work, that Franco and Manzini (2017b) extend the 'inclusion' account to the other oblique morpheme most likely to appear as an inflectional case marker from a crosslinguistic viewpoint (see Caha 2009), namely the instrumental; in Italian, the instrumental is lexicalized by the preposition con (with). We follow Franco and Manzini (2017b) in using the cover term 'instrumental' for all the semantic flavors that may be introduced by with like morphemes (see Stolz et al 2006 for a full typological survey). Franco and Manzini (2017a)'s starting point is the observation originally developed in Levinson (2011), i.e., possession/inclusion relations can be realized by with morphemes at the level of noun phrases (cf.…”
Section: Vp Dato [Predp Le Mele [[⊆ A] Gianni ]]]mentioning
confidence: 99%
See 1 more Smart Citation
“…2 It is important to notice, for the purposes of our work, that Franco and Manzini (2017b) extend the 'inclusion' account to the other oblique morpheme most likely to appear as an inflectional case marker from a crosslinguistic viewpoint (see Caha 2009), namely the instrumental; in Italian, the instrumental is lexicalized by the preposition con (with). We follow Franco and Manzini (2017b) in using the cover term 'instrumental' for all the semantic flavors that may be introduced by with like morphemes (see Stolz et al 2006 for a full typological survey). Franco and Manzini (2017a)'s starting point is the observation originally developed in Levinson (2011), i.e., possession/inclusion relations can be realized by with morphemes at the level of noun phrases (cf.…”
Section: Vp Dato [Predp Le Mele [[⊆ A] Gianni ]]]mentioning
confidence: 99%
“…(4) La donna con i bambini the woman with the children 'The woman with the children' Franco and Manzini (2017b) demonstrated that with-like inflections/prepositions express the reverse relation with respect to genitive and dative morphemes, given that the inclusee, rather than the inclusor, is introduced by the oblique case/adposition. Thus, for these with-like morphemes, they introduce the (⊇) label and content, as shown in the example (5).…”
Section: Vp Dato [Predp Le Mele [[⊆ A] Gianni ]]]mentioning
confidence: 99%
“…However the discussion to follow goes through if the ergative is conceptualized as an instrumental or other elementary relator (cf. Franco & Manzini 2017).…”
Section: The Agreement Of Structural Obliques Parametermentioning
confidence: 99%
“…This second option would be compatible with the ⊇ operator (i.e. the reverse of ⊆) proposed by Franco & Manzini (2017), too, although they restrict its occurrence mainly to instrumentals contexts. Despite the differences across these accounts, they all essentially share the idea that relational heads are to be regarded predicatively: this is in line with the approaches to p in the extended PP.…”
Section: The Spatial Componentmentioning
confidence: 99%
“…Other constructions reduced to ⊆ are: have auxiliary(Manzini & Savoia 2011: chapter 6); dative, genitive, and ablative case, possessives, and the corresponding inflectional morphology(Manzini & Savoia 2011: chapter 8;Franco et al 2015;Manzini & Franco 2016); obliques(Franco et al 2021). Moreover,Franco & Manzini (2017) argue that instrumentals instantiate the inverse relation, i.e. superset-of '⊇'.…”
mentioning
confidence: 99%